임상유전자검사 및 차세대 염기서열분석을 위한 임상병리사의 역할 - 진현석; Hyun-seok Jin; 박상정; Sangjung Park; 안미숙; Mi-sook Ahn; 박상욱; Sangwook Park (Korean journal of clinical laboratory science, 2023)
코로나19가 창궐한 후 임상병리사(medical technologists, MT)가 병원에서 PCR 검사를 수행하고 있을 뿐만 아니라 차세대 염기서열분석(next-generation sequencing, NGS)도 수행한다는 사실을 일반적으로 알고 있다. 하지만, 많은 사람들은 유전자검사 분야에 대한 임상병리사의 업무로 의료법에 명시되어 있지 않다는 사실을 인지하지 못하고 있는 실태이다(MT 72.5%, N=200; 학생 62.8%, N=123). 이러한 이유로, NGS에 대한 임상병리사의 업무 적절성을 검증하기 위해서 온라인 설문지를 작성하도록 설계하여 설문조사 결과를 분석하였다. NGS가 포함된 유전분야에 대한 임상병리사의 업무범위에 대한 법제화가 필요하다(MT 99.5%, N=200, 학생 86.8%, N=123)고 나타났다. 그리고 임상병리사 국가면허시험 문제은행에 세포유전학 및 분자유전학 관련 임상유전학 문항이 모두 포함돼야 한다(MT 97.5%, N=200; 학생 72.3%, N=123)고 조사되었다. 이러한 조사를 바탕으로 임상병리학 분야의 발전을 위해 임상병리사와 학생 모두를 위한 유전자 교육 및 법제화를 위해 대한임상병리사협회는 교수협의회와 적극 협력할 필요가 있겠다. Since the coronavirus disease-2019 (COVID-19) outbreak, it has been generally believed that a medical technologists (MTs) are supposed to perform polymerase chain reaction tests and next-generation sequencing (NGS) in the hospitals. However, many do not recognize that the duty of MT for clinical genetic testing has not been stated in the Medical Laws (72.5% for MT, N=200; 62.8% for students, N=123). In this regard, to evaluate the feasibility of MT’s role for NGS genetic testing, we requested our subjects to fill out an online survey and analyzed the data. Among them, it shows that the scope of MT’s role, including NGS performance should include clinical genetic testing (99.5% for MT, N=200; 86.8% for students, N=123). Also, questions on clinical genetics, which is associated with both cellular genetics and molecular genetic questions should be included in the National MT License Problem Bank (97.5% for MT; 71.4% for students). Based on these results, the Korean Association of Medical Technologists needs to cooperate synergically with the Academic Association of Biomedical Laboratory Science with respect to genetic education and legislation for the future benefit of both MTs and students.